Navigating Socialist Encounters Moorings and (Dis)Entanglements between Africa and East Germany during the Cold War - Burton, Eric; Dietrich, Anne; Harisch, Immanuel; Schenck, Marcia (Africa in Global History, 2021)
This edited volume firmly places African history into global history by highlighting connections between African and East German actors and institutions during the Cold War. With a special focus on negotiations and African influences on East Germany (and vice versa), the volume sheds light on personal and institutional agency, cultural cross-fertilization, migration, development, and solidarity.